2020
DOI: 10.3390/ijerph17041369
|View full text |Cite
|
Sign up to set email alerts
|

Is Alcohol Consumption Associated with Poor Perceived Academic Performance? Survey of Undergraduates in Finland

Abstract: The relationship between academic performance and alcohol consumption among students remains inconsistent. We assessed this relationship, controlling for sociodemographic characteristics across seven faculties at the University of Turku (1177 undergraduates). An online questionnaire assessed: seven sociodemographic characteristics (age, gender, year/discipline of study, accommodation type, being in intimate relationship, parental education, and income sufficiency); two perceived academic performance (students’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 84 publications
6
31
3
1
Order By: Relevance
“…A study by Herrero-Montes et al (2019) found no significant relation between cognitive performance and alcohol consumption among university students. Similar results have been observed by El Ansari W et al (2020) in Finland.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A study by Herrero-Montes et al (2019) found no significant relation between cognitive performance and alcohol consumption among university students. Similar results have been observed by El Ansari W et al (2020) in Finland.…”
Section: Discussionsupporting
confidence: 91%
“…(2019) found no significant relation between cognitive performance and alcohol consumption among university students. Similar results have been observed by El Ansari and Salam (2020) in Finland. However, in this study academic performance was evaluated through the student's own subjective perception.…”
Section: Discussionsupporting
confidence: 90%
“…Early onset of alcohol consumption [ 18 ], prior drinking experiences [ 19 ], parental educational level [ 20 ], living away from parental home [ 21 ], positive alcohol expectancies [ 22 ], peer drinking [ 23 ] and pregaming [ 24 ] (i.e., drinking before going out) have been recognized as risk factors for the excessive use of alcohol and the misuse of other drugs among students [ 21 , 22 , 23 , 24 ]. Parental alcohol consumption and parental permissibility of alcohol use are also associated with student alcohol consumption [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests knowledge gaps. Whilst some recent studies exist concerning alcohol consumption among university students in Finland [ 38 ], the very few studies that examined IDU among Finnish university students are quite outdated. For instance, in the 90s, 3.6% of female and 3.1% of male students reported the mixed use of psychiatric drugs and alcohol with the aim of getting high, at least once [ 39 ].…”
Section: Introductionmentioning
confidence: 99%